Parameters of the anatomical marks of the mental nerve hole for oral surgery - Delgadillo-Ávila, Juana (2015)
The mental nerve (MN) is one of the anatomical structures important to identify, preserve and avoid injure. The knowledge of the layout and anatomical variants of MN is imperative for the performance of surgical procedures involving the chin area. Objective: The purpose of this study was to determine, the location and frequency of emergency hole of MN, accessories nerves, presence of loops and their relations with the alveolar ridge and the mandibular border, by observing prepared anatomical human corpses. Methodology: 31 mandibles of corpses were dissected. Results: It was found that the most frequent distance between the emergency MN with respect to the mandibular alveolar ridge was the range of 11 to 15.5 mm at 57.6% and 11 to 15.5 mm in 72.7% respectively. NM’s relationship with respect to the teeth was that 63.6% of the cases is at the same height of the PMI 2a, 18.2% had accessory mental nerve and the most frequent location was upper than MN in 66.7% of the cases; the presence of loops was not found. Conclusion: the MN hole emergency occurs mostly below the PMI 2a in 63.6% of peruvian people, which coincides with the majority of investigations. The presence of accessories MN was found in 18%, which is higher compared to other studies, so greater care in surgeries in the chin area is recommended.